2023
DOI: 10.1080/10717544.2023.2171158
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pt(IV) prodrug self-assembled nanoparticles with enhanced blood circulation stability and improved antitumor capacity of oxaliplatin for cancer therapy

Abstract: Pt(IV) compounds are regarded as prodrugs of active Pt(II) drugs (i.e. cisplatin, carboplatin, and oxaliplatin) and burgeoned as the most ideal candidates to substitute Pt(II) anticancer drugs with severe side effects. Nanoparticle drug delivery systems have been widely introduced to deliver Pt(IV) prodrugs more effectively and safely to tumors, but clinical outcomes were unpredictable owing to limited in vivo pharmacokinetics understanding. Herein, a novel Pt(IV) prodrug of oxaliplatin(OXA) was synthesized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…These are the most extensively studied and clinically utilized metallodrugs in cancer therapy. This group includes first-generation cisplatin ( Johnstone et al, 2016 ), second-generation carboplatin ( Devanabanda and Kasi, 2023a ), third-generation oxaliplatin ( Devanabanda and Kasi, 2023b ), and novel platinum nanoparticled complexes ( Fu et al, 2023 ). By forming DNA adducts induced apoptosis, these platinum-based drugs exert their anti-cancer effects with varying pharmacokinetics, toxicity profiles, resistance mechanisms, and therapeutic indications.…”
Section: Resultsmentioning
confidence: 99%
“…These are the most extensively studied and clinically utilized metallodrugs in cancer therapy. This group includes first-generation cisplatin ( Johnstone et al, 2016 ), second-generation carboplatin ( Devanabanda and Kasi, 2023a ), third-generation oxaliplatin ( Devanabanda and Kasi, 2023b ), and novel platinum nanoparticled complexes ( Fu et al, 2023 ). By forming DNA adducts induced apoptosis, these platinum-based drugs exert their anti-cancer effects with varying pharmacokinetics, toxicity profiles, resistance mechanisms, and therapeutic indications.…”
Section: Resultsmentioning
confidence: 99%
“…41) to form self-assembled micellar nanoparticles (PEG-OXA NPs). 144 The cytotoxicity in HT29 cells was found to be 1.7-fold lower than oxaliplatin alone (6.12 μM) at 48 h. In vitro , PEG-OXA NPs remained stable in plasma but rapidly released oxaliplatin in HT29 tumor cells. In vivo , pharmacokinetic studies demonstrated a long circulation of the nanoparticles with a low concentration of oxaliplatin in plasma upon PEG-OXA NPs administration.…”
Section: Oxaliplatin-based Pt(iv) Prodrugsmentioning
confidence: 88%
“…41) to form selfassembled micellar nanoparticles (PEG-OXA NPs). 144 The cytotoxicity in HT29 cells was found to be 1.7-fold lower than oxaliplatin alone (6.12 μM) at 48 h. In vitro, PEG-OXA NPs remained In another example, a prodrug vesicle (NP2) for ICD-based cancer chemoimmunotherapy was reported. 145 The vesicles comprised an oxaliplatin prodrug HODAan hexadecyl-oxaliplatin diethylene amine modified with the acid-sensitive 2,3dimethylmaleic anhydride (compound 106, Fig.…”
Section: Nanoparticle-based Approachesmentioning
confidence: 97%
“…Pt(IV), the oxidized state of divalent platinum, is a focal point in the research and development of novel platinum-based drugs. Pt(IV) compounds offer several advantages: (1) Improved drug stability: Pt(IV) compounds exhibit good stability, reducing drug degradation and inactivation in the body, thus prolonging the drug's half-life [13,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Pt(IV), the oxidized state of divalent platinum, is a focal point in the research and development of novel platinum-based drugs. Pt(IV) compounds offer several advantages: (1) Improved drug stability: Pt(IV) compounds exhibit good stability, reducing drug degradation and inactivation in the body, thus prolonging the drug’s half-life [ 13 , 15 , 16 , 17 ]. (2) Increased selectivity: Pt(IV) compounds can selectively target specific tumors by tailoring their ligand structure and chemical properties, minimizing toxicity to normal cells [ 18 ].…”
Section: Introductionmentioning
confidence: 99%